EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN FISIKA BERBANTUAN ANIMASI KOMPUTER TERHADAP HASIL BELAJAR SISWA SMA NEGERI 3 TAMBUSAI ROKAN HULU RIAU - Panjaitan, Meliana; Febriani, Yeza; Hatika, Rindi Genesa (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2015)
The purpose of this research to know in the effectiveness of learning on use media with the assistance of a computer animation on the results of the student learning. The research methods was pre-experiment with one group pretest-posttest design. Data collection techniques used a test. The sample collection technique was purposive the sampling method, with samples were class XA SMAN 3 Tambusai. Variable free was the use of media learning computer animation, while bound namely variable was student result. An instrument in this research were implementation plan of learning lesson plans, the syllabus and the test. Gain score is lowest was 0,40 (medium) while the value of the gain score is biggest 0,92 (big). The result of average gain score was 0,73 (big). The results of research can be concluded that media learning with the assistance of a computer animation effective used on the subjects of physics.